Antenatal Corticosteroids in the Late Preterm Period. Issue 5 (September 2016) - Wisner, Kirsten
Abstract : Results of a recent multicenter randomized clinical trial found less respiratory morbidity among newborns when their mothers who were at risk for preterm birth from 34 weeks and 0 days up to 36 weeks and 5 days gestation were given antenatal betamethasone. Therefore the Society for Maternal-Fetal Medicine now recommends that women at risk for late preterm birth be given antenatal steroids using a suggested protocol for dosing, appropriate candidates, and gestational dating criteria to reduce respiratory morbidity among late preterm babies.